2001
DOI: 10.1076/ocii.9.4.219.3957
|View full text |Cite
|
Sign up to set email alerts
|

Short-term chlorambucil for refractory uveitis in Behcet's disease

Abstract: Short-term chlorambucil therapy for refractory uveitis in Behcet's disease is effective in controlling the disease in two-thirds of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 9 publications
0
16
0
1
Order By: Relevance
“…A retrospective study of BD patients with refractory uveitis treated with short-term chlorambucil improved ocular involvement in 2/3 of cases and reduced the number of attacks [97].…”
Section: Alkylating Agents (Chlorambucil and Cyclophosphamide)mentioning
confidence: 99%
“…A retrospective study of BD patients with refractory uveitis treated with short-term chlorambucil improved ocular involvement in 2/3 of cases and reduced the number of attacks [97].…”
Section: Alkylating Agents (Chlorambucil and Cyclophosphamide)mentioning
confidence: 99%
“…Uncontrolled case series make up most of the evidence for the effectiveness of cyclophosphamide and chlorambucil in uveitis [129, 130, 131, 132]. Only one randomised controlled trial was found that compared the efficacy of prednisolone, azathioprine and cyclophosphamide for treating idiopathic uveitis in 32 patients: azathioprine was found to be more effective of the three in controlling inflammation [133].…”
Section: Treatment Optionsmentioning
confidence: 99%
“…47,58,87,92,[155][156][157][158][159][160][161][162] Remission was achieved in 70% of patients treated with chlorambucil with an average follow-up of 4 years. Forty-seven percent had at least 2 lines of improvement in Snellen visual acuity.…”
Section: Chlorambucil/leukeranmentioning
confidence: 99%